Improved harmonization of eosin‐5‐maleimide binding test across different instruments and age groups. Issue 6 (10th October 2015) - Agarwal, Archana M.; Liew, Michael A.; Nussenzveig, Roberto H.; Sangle, Nikhil; Heikal, Nahla; Yaish, Hassan; Christensen, Robert
Abstract : Background: The eosin‐5′maleimide (EMA) binding test has been studied extensively for the detection of hereditary spherocytosis (HS). Its performance characteristics have been compared to NaCl‐based or glycerol lysis‐based red cell osmotic fragility tests and cryohemolysis. HS samples are also better identified when both mean channel fluorescence (MCF) of EMA relative to controls and the coefficient of variation (CV) are analyzed. Methods: We looked at 65 normal controls including 30 adults 25‐65 years old and 35 newborns and 12 HS cases. In addition to the MCF and the CV, we used a side scatter (SSC) vs. EMA fluorescence gate or "footprint" to depict where normal erythrocytes should appear. Erythrocytes that have reduced band 3 protein appear outside of the footprint. Results: In our study, newborn data did not cluster with the samples from working age individuals. The MCF and the CVs of normal newborns were higher than normal adult group. However, the footprint data of normal samples relative to their controls was around 99.5% for each group, because the footprint was moved to fit the pattern of the normal. Conclusions: The inclusion of footprint parameter will help in better standardization as well as implementation of this test across different age groups as well as different instruments. © 2015 International Clinical Cytometry Society